Leadership, Learning Organization and Job Satisfaction in Ghanaian Telecommunications Companies - Remy Nyukoron (European Scientific Journal, ESJ, 2016)
This survey aims to explore the relationship between leadership and learning organization dimensions on employee job satisfaction. The sample involved staff working in the top telecom companies operating in Ghana. Data were gathered utilizing a structured questionnaire; a total of 700 questionnaires were distributed and 500 valid responses were returned. The data were processed using exploratory factor analysis as well as multiple linear regression. The study findings revealed a positive impact of interactive learning organization building blocks on employee job satisfaction. The results also indicated leadership behaviors to cause significant positive impact on learning organizations. With the growing number of knowledge workers in Ghana, it is not possible for business executives to satisfy the demands of employees through conventional leadership. Rather, business executives need to enhance their own skills in transformational leadership, setting a good example, encouraging continuous learning and innovative activities, developing the potentials of their employees, providing training and education and offering monetary incentives, as these are necessary to keep people with excellent talents. Thus, this study effort, for the first time, raises the awareness of Ghanaian business organizations of the effect of leadership and learning organization practices on job satisfaction.